2011
DOI: 10.1007/s10865-011-9372-2
|View full text |Cite
|
Sign up to set email alerts
|

UV photography, masculinity, and college men’s sun protection cognitions

Abstract: This study examined the impact of an ultraviolet (UV) photography intervention and masculinity on college men's sun protection cognitions, including: perceived vulnerability to skin damage, attitudes toward sun protection, willingness to engage in sun protection behaviors, and intentions to receive a skin cancer exam. After completing a baseline survey, participants (N = 152) viewed a black-and-white photo of their face. Half also viewed a photo showing their UV damage. Participants then completed a second sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 57 publications
0
28
0
Order By: Relevance
“…In addition one study was a grey literature paper, identified from the clinical trials registry (clinicaltrials.gov) [51]. The number of studies targeting each risk behaviour included 27 (27%) for physical inactivity [5278], 25 (25%) for alcohol use [6589], 21 (21%) for unsafe sexual behaviour [51, 79–98], 5 (5%) for poor diet [99103], 5 (5%) for unsafe vehicle driving [104108], 4 (4%) for tobacco smoking [109112], 2 (2%) for recreational drug use [113, 114] and 1 (1%) for tanning/sun exposure [115]. There were 10 studies (10%) that assessed multiple risk behaviours [116125] (of these 3 studies targeted poor diet and physical inactivity [120, 122, 123], 2 studies targeted alcohol use and recreational drug use [117, 121], 1 study targeted alcohol use and unsafe sexual behaviour [118], 1 study targeted poor diet, physical inactivity and tobacco smoking [116], 1 study targeted tobacco smoking, alcohol use and recreational drug use [119], 1 study targeted alcohol use and physical inactivity [125] and 1 study targeted unsafe vehicle driving and alcohol use [124]).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition one study was a grey literature paper, identified from the clinical trials registry (clinicaltrials.gov) [51]. The number of studies targeting each risk behaviour included 27 (27%) for physical inactivity [5278], 25 (25%) for alcohol use [6589], 21 (21%) for unsafe sexual behaviour [51, 79–98], 5 (5%) for poor diet [99103], 5 (5%) for unsafe vehicle driving [104108], 4 (4%) for tobacco smoking [109112], 2 (2%) for recreational drug use [113, 114] and 1 (1%) for tanning/sun exposure [115]. There were 10 studies (10%) that assessed multiple risk behaviours [116125] (of these 3 studies targeted poor diet and physical inactivity [120, 122, 123], 2 studies targeted alcohol use and recreational drug use [117, 121], 1 study targeted alcohol use and unsafe sexual behaviour [118], 1 study targeted poor diet, physical inactivity and tobacco smoking [116], 1 study targeted tobacco smoking, alcohol use and recreational drug use [119], 1 study targeted alcohol use and physical inactivity [125] and 1 study targeted unsafe vehicle driving and alcohol use [124]).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 100 included studies, 46 included young male participants only with 18 (18% of total studies and 39.1% of young adult male only studies) [5254, 57, 58, 60, 61, 6473, 76] for physical inactivity, 14 (14% of total studies and 30.4% of young adult male only studies) for unsafe sexual behaviour [51, 80, 82, 8591, 94, 96–98], 4 (4% of total studies and 8.7% of young adult male only studies) for alcohol use [126129], 2 (2% of total studies and 4.3% of young adult male only studies) for unsafe vehicle driving [104, 105] 1 (1% of total studies and 2.2% of young adult male only studies) for tobacco smoking [110], 1 (1% of total studies and 2.2% of young adult male only studies) for poor diet [103], and 1 (1% of total studies and 2.2% of young adult male only studies) for tanning/sun exposure [115]. Also 5 (5% of total studies and 10.9% of young adult male only studies) of the studies with only young adult male participants targeted multiple risk behaviours [116, 119, 122, 124, 125].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…BW has been measured in research on several health risk behaviors including drug use (Gibbons et al, 2010) and risky sex (Stock, Gibbons, Peterson, & Gerrard, 2013;Roberts, Gibbons, Kingsbury, & Gerrard, 2013), and health-promoting behaviors such as smoking cessation (Gerrard, Gibbons, Lane, & Stock, 2005), and sun protection (Matterne, Diepgen, & Weisshaar, 2011;Walsh & Stock, 2012). In many cases, willingness to engage in a certain behavior is an independent predictor of actual behavior in the future (controlling for more deliberate intentions to engage in the behavior) (Gerrard et al, 2008).…”
Section: Behavioral Willingnessmentioning
confidence: 99%